So That It May Be Lived: The Theatrical Conception in María Zambrano’s Thought - Rodríguez Roríguez, Nieves (Escritura e Imagen, 2024)
María Zambrano's relationship with theater, in its political and metaphysical dimension, is a constant in the life and thought of the philosopher. After the experience of exile, Antigone appears to her, the tragic heroine who will accompany her for more than twenty years—in which she investigates time, dreams, delirium, democracy or piety—and who will bear fruit in her play La tumba de Antígona (1967). This paper, therefore, aims to illuminate these relationships and the reception of thought in current contemporary theater.
Keywords: María Zambrano; dramatic literature; exile; Antígona